Shallow Water Depths Mapping Using ALOS "“ AVNIR Satellite Imagery at Pari Islands, Seribu Archipelago, Jakarta - Sanova, Aulia Seto Sandi; Saputro, Siddhi; Helmi, Muhammad (Jurnal Laut Khatulistiwa, 2018)
Pari Island has wide shallow water area. Very shallow condition mapping method need more time.satelite remote sensing technology now can be to use mapping shallow water area faster and easier. Aims of this research are mapping the shallow water area and knowing ALOS-AVNIR satellite imagery abilities.This research was done at May "“ July 2009 and the field survey was done at Pari Island  June 8th "“ 22nd 2009. Materials that use acquired 30th April 2008 ALOS-AVNIR satellite imagery and water depth data. This research was using descriptive method. Jupp 1988 method was use to classify the imagery. Water depth data was captured by Echosounder and measure stick.Classification of shallow water depth resulted 5 classes of depth generally, Those depth classes are 0"“0.5 m, 0.5"“1m, 1-3 m, 3-5m, 5-10m, and 10m. Accuration test showed that ALOS-AVNIR satellite imaging acquired 30th April 2008 able to result a good information of shallow water depth.